ROLE OF GENE EXPERT/MTB TEST IN CHILDHOOD TUBERCULOSIS - Aisha Sajid; Sohaib Riaz (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: To evaluate the role of Gene Expert/MTB test in diagnosing childhood tuberculosis and resistance to Rifampicin.METHODS AND PATIENTS: It was a cross sectional observational study conducted at the Department of Pediatrics, Madina Teaching Hospital, Faisalabad, during a period of 9 months i.e., July 2016 to March2017. A total number of 65 patients suspected of having pulmonary or extra pulmonary tuberculosis on the basis of history and examination, were included in the study. They were evaluated by routine lab investigations for diagnosis of tuberculosis (CBC, ESR,Mantoux test, Xray chest, FNAC lymph nodes etc) as well as by gene expert MTB/RIF test performed on sample taken from the area of involvement. The ﬁndings were recorded on a predesigned proforma. Data was analyzed by SPSS version 23. P value <0.05 was considered signiﬁcant. RESULTS: Out of total 65 suspected cases, 40 turned out to be tuberculosis fulﬁlling the criteria of PPA scoring chart. Mean age of our patients was 9.35± 4.34. Eighteen patients (45%) showed detection of mycobacterium tuberculosis by Gene Expert/MTB/RIF assay, while 22 patients had negative result. Overall sensitivity of the test was 55 % where as speciﬁcity was 81%. Detection of mycobacterium was signiﬁcantly associated with the sample site (p value = 0.003). Rifampicin resistance was not found in any of the patients.CONCLUSION: Gene Xpert/MTB/RIF is quite helpful in diagnosing the childhood tuberculosis with 81% speciﬁcity but variable sensitivity depending upon the sample site. Maximum sensitivity was found for lymph node aspirate.